The impact of instagram influencer characteristics on purchasing intention of fashion product in Klang Valley - Pavitra, Munian (2022)
Social media had emerged as a powerful instrument for marketing, allowing for quick, democratic, and user-generated dissemination. As a result, the fashion industry uses it to analyse trends and forecast fashion habits. Social Media Influencer (SMI) has an influential power correlation in forming the image of a product and encouraging the increase of shopper purchase interest since they efficiently communicate with their followers through advanced media. As a result of this awareness and consideration, fashion industry industries and businesses have concentrated their efforts on selecting the most relevant factors that effectively influence consumers into buying fashion products on social media in order to make a competitive advantage from new and existing competitors in the market. This study attempted to identify social media influencer personal characteristic that have a significant relationship with fashion products purchase intention among residents in Klang Valley using Social Learning Theory and the Source Credibility and Source Attractiveness Models. This study looked at four independent variables: trustworthiness, expertise, familiarity and similarity. By adopting proportionate sampling, 300 sets of questionnaire were distributed around Klang Valley. As findings its revealed that trustworthiness, expertise, and familiarity have a significant relationship toward purchase fashion products on Instagram. However, similarity variable has no significant relationship toward purchasing intention. Among all variables, familiarity of Instagram influencer toward has the greatest impact on their fashion products purchase intention on Instagram.